Representing Blackness : Issues in Film and Video - Smith, Valerie, 1956- (Book collections on Project MUSE., 1997)
The essays in this collection provide a variety of perspectives on black representation and questions of racial authenticity in mainstream as well as African American independent cinema. This volume includes seminal essays on racial stereotypes, trenchant critiques of that disclosure, original essays on important directors such as Haile Gerima and Charles Burnett, and an insightful discussion of black gay and lesbian film and video.